Two new genera of Laophontidae (Copepoda: Harpacticoida) without sexual dimorphism in the endopods of the swimming legs - Gheerardyn, Hendrik; Fiers, Frank; Vincx, Magda; de Troch, Marleen (Zootaxa, 2006)
Two new monospecific genera of the harpacticoid family Laophontidae T. Scott, 1905 are described here. Apistophonte wasiniensis gen. et sp. n. was found along the Kenyan coast and Propephonte duangitensis gen. et sp. n. along the northern coast of Papua New Guinea. They differ from most other laophontid genera in the absence of sexual dimorphism in the endopods of the swimming legs. At first sight, both new species resemble each other very closely in habitus, integumental ornamentation, chaetotaxy of the swimming legs and absence of sexual dimorphism in the endopods. However, the detailed characteristics of A1, maxilla and male P5 show that the species are not congeneric. The structure of the first antennular segment of Propephonte gen. n. suggests a close relationship with Peltidiphonte Gheerardyn and Fiers, 2006. The exact affinities of Apistophonte gen. n. however remain difficult to assess.